Effect of Vasoactive Intestinal Peptide (VIP) on NKG2D Signal Pathway and Its Contribution to Immune Escape of MKN45 Cells - Chong Wang; Xi-Jin Zhou; Yuan-yuan Li; Juan Wan; Le-ying Yang; Guo-Hua Li (The Scientific World Journal)
Objective. To investigate VIP effect on the cytotoxicity of NK cell to gastric cancer cells in vitro and the relation between the effect with the NKG2D signal molecules in NK cells. Material and Methods. NK cells were purified from peripheral blood mononuclear cells (PBMC). Before and after NK cells were incubated with VIP or its antagonist (D-p-Cl-Phe6,Leu17)-VIP, we detected the cytotoxicity of NK cells to MKN45 gastric cancer cells by MTT and detected the expressions of NKG2D, DAP10, and NF-κB proteins and mRNAs in NK cells by immunocytochemistry and RT-PCR in those conditions. Then we analyzed the effect of VIP and its antagonist on the cytotocicity of NK cell to gastric cancer cells and on expressions of NKG2D, DAP10, and NF-κB signal molecules in NK cells. Results. VIP could inhibit the cytotoxicity of NK cells to MKN45 cells and could inhibit the expressions of NKG2D, DAP10, and NF-κB in NK cells. However, (D-p-Cl-Phe6, Leu17)-VIP could reverse those effects. Conclusions. The VIP inhibited the cytotoxicity of NK cell to MKN45 cells which might get through inhibiting the expressions of NKG2D signal molecules in NK cells. This may be one mechanism of gastric cancer cells escaping organism immune clearance.